Engaged pedagogy through role-play in a Buddhist studies classroom - Garrett, Frances Mary (Teaching theology and religion, 2018)
The article discusses two versions of a complex role-playing exercise in undergraduate courses on Buddhism. The pedagogical exercise demonstrated how imagination cultivated through creative writing could be used to enhance learning about history, culture, and religion. Students were also challenged to generate an understanding of religious practice that arose from both cognitive and sensory learning. The project showed that by interacting with a form of engaged pedagogy that worked with the imagination, without leaving the classroom students developed a deep care for and active engagement with communities located spatially and temporally far from home. With empathy and critical reflection, they came to see how religious meaning is constructed at a communal level through embodied action and emotional sensibility.